Mapping The Cultural Landscape of Tumori Village, West Gunungsitoli - Shindi Indira, Sri; D. Machmoed, Bachtiar; J. Hia , Natalia; Supriyadi, Supriyadi (International Journal of Science, Technology & Management, 2023)
Tumöri Village is one of nine villages located in West Gunungsitoli District, West Gunungsitoli City, North Sumatra Province. Tumöri Village has various potentials that have not been explored and developed optimally. The natural and cultural resources in the village of Tumöri are hills and forest gardens covering an area of more than 5 hectares, the Mola river flow, beautiful natural scenery, and the presence of 10 traditional Nias houses, along with various other potential cultural arts. For this reason, research is needed to see the potential for natural and cultural tourism, a reference for tourism development in an area like Tourism Villages. Tourism Village includes aspects of developing tourism destinations based on local village wisdom, business development, and tourism industry based on community economy, tourism marketing development, and tourism institutions.